INCORPORAÇÃO DAS CINZAS DOS RESÍDUOS SÓLIDOS DA INDÚSTRIA DE EUCALIPTO NA PRODUÇÃO DE MICROCONCRETOS - NEVES, Évelin Caroline Miguel; SANTOS, Jacielle Elias dos; OLIVEIRA, Rony Gonçalves de; ALVES, Aguinaldo Lenine; ZANFOLIM, Antonio Aparecido (ANAIS DO ENIC, 2017)
-